1999
DOI: 10.1055/s-1999-14053
|View full text |Cite
|
Sign up to set email alerts
|

Antimycobacterial Ergosterol-5,8-endoperoxide from Ajuga remota

Abstract: In a bioassay-guided search for antimycobacterial natural products from higher plants, we have chemically investigated the methanol extract of aerial parts of Ajuga remota Benth. (Labiatae) for its active constituent(s). Bioactive chromatographic fractions of the crude extract provided the known triterpene ergosterol-5,8-endoperoxide plus the diterpenes clerodin, ajugarin-I, and ajugarin-II, which had been previously isolated from A. remota. This is the first report on the isolation of ergosterol-5,8-endoperox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

5
57
0
1

Year Published

2002
2002
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 70 publications
(63 citation statements)
references
References 0 publications
5
57
0
1
Order By: Relevance
“…Among the sterols tested, compounds 2-7 exhibited activity with MIC values of 1-51 mg/ml, among which ergosterol peroxide (2; MIC 1 mg/ml) 15) followed by cerevisterol (3; 6 mg/ml) and 6-epicerevisterol (4; 11 mg/ml) showed the most potent activity, although still being an order of magnitude less potent than the first-line antitubercular drug, ri- fampin (Table 1). From the limited data set, it appears that C6a,8a-epidioxidation (2), hydroxylation at both C-5a and C6a/b (3-6), or hydroxylation at C-7b accompanied with C5a,6a-epoxidation (7) gives rise to higher activity for the 3b-hydroxy sterols.…”
Section: Ebv-ea Induction Testsmentioning
confidence: 99%
See 2 more Smart Citations
“…Among the sterols tested, compounds 2-7 exhibited activity with MIC values of 1-51 mg/ml, among which ergosterol peroxide (2; MIC 1 mg/ml) 15) followed by cerevisterol (3; 6 mg/ml) and 6-epicerevisterol (4; 11 mg/ml) showed the most potent activity, although still being an order of magnitude less potent than the first-line antitubercular drug, ri- fampin (Table 1). From the limited data set, it appears that C6a,8a-epidioxidation (2), hydroxylation at both C-5a and C6a/b (3-6), or hydroxylation at C-7b accompanied with C5a,6a-epoxidation (7) gives rise to higher activity for the 3b-hydroxy sterols.…”
Section: Ebv-ea Induction Testsmentioning
confidence: 99%
“…From the limited data set, it appears that C6a,8a-epidioxidation (2), hydroxylation at both C-5a and C6a/b (3-6), or hydroxylation at C-7b accompanied with C5a,6a-epoxidation (7) gives rise to higher activity for the 3b-hydroxy sterols. On the other hand, two compounds, hypsizprenol A 9 (8; MIC 15 mg/ml) and hypsiziprenol BA 10 (12; 44 mg/ml), showed potent antitubercular activity among the eight hypsiziprenols (8)(9)(10)(11)(12)(13)(14)(15) tested. There was no apparent correlation between the structures and antitubercular activity for the hypsiziprenols.…”
Section: Ebv-ea Induction Testsmentioning
confidence: 99%
See 1 more Smart Citation
“…4) EPO has significant cytotoxic activity. [5][6][7][8] Recent pharmacological studies have demonstrated that EPO also possesses immunosuppressive, 9) human T lymphocyte inhibitory, 10) anti-inflammatory, 11) phospholipase A 2 inhibitory, anti-atherosclerosis 12) apoptosis-inducing, 13) DNA topoisomerase inhibitory, 14,15) anticomplementary, 16) anti-viral, 17) anti-mycobacterial, 18) antibacterial, 19) sulfatase inhibitory, 20) and aldose reductase inhibitory 21) effects. Various mushrooms have been used as traditional or folk medicines for a long time.…”
mentioning
confidence: 99%
“…It has numerous beneficial effects such as panacea (cure-all), [10] gastrointestinal disorders, [11] hypertension, diabetes, [12] anthelmintic and antiinflammatory. [13] The plants of the genus Ajuga have been reported to have antifungal, antibacterial, [14][15] antimycobacterial, [16] antihypertensive, [17] antiplasmodial, [18] hypoglycaemic, [19] larvae and insect antifeedant activitis. [13,[20][21] Nevertheless, antiarthritic activities for Ajuga iva have never been proved.…”
Section: Introductionmentioning
confidence: 99%